2008
DOI: 10.1115/1.2804933
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of the Available Ammonia Horizontal In-Tube Flow Boiling Heat Transfer Correlations for Liquid Overfeed Evaporators

Abstract: The aim of this work is to present a critical examination of both the available experimental data and the performance of the available heat transfer correlations for oil-free ammonia horizontal in-tube boiling at fin-and-tube-type air-to-refrigerant liquid overfeed evaporation conditions. First, a selection and comparison of the experimental database found in the open literature at the mentioned working conditions is presented. Subsequently, after a short description of the most relevant heat transfer correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Kelly et al [1] carried out a work centered on the study of ammonia evaporation at air coil conditions, and their comparison against previous available correlations, which was found unsatisfactory. Ablanque et al [11] have reported a critical examination of available experimental data on ammonia for this range (showing important divergences between datasets), and have carried out a revision of the performance of the available correlations, which also show considerable discrepancies. Bjork and Palm [2] have recently investigated the effect of turn bends on the stratified flow through a non-circular tube of a domestic refrigerator evaporator.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kelly et al [1] carried out a work centered on the study of ammonia evaporation at air coil conditions, and their comparison against previous available correlations, which was found unsatisfactory. Ablanque et al [11] have reported a critical examination of available experimental data on ammonia for this range (showing important divergences between datasets), and have carried out a revision of the performance of the available correlations, which also show considerable discrepancies. Bjork and Palm [2] have recently investigated the effect of turn bends on the stratified flow through a non-circular tube of a domestic refrigerator evaporator.…”
Section: Introductionmentioning
confidence: 97%
“…Honda and Wang [12] have presented an advanced theoretical model for the prediction of heat transfer in stratified flow within these kind of tubes. In the present paper, the flowpattern map based correlation proposed by Thome [13] has been used due to the conclusions found in Ablanque et al [11], and because it allows an accurate evaluation of the dry angle and the corresponding dry/wet heat transfer coefficients, which could be integrated with the angular tube discretisation approach. This paper is devoted to the presentation of a novel model of finand-tube evaporators.…”
Section: Introductionmentioning
confidence: 98%